2015
DOI: 10.1016/j.nicl.2015.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Less efficient and costly processes of frontal cortex in childhood chronic fatigue syndrome

Abstract: The ability to divide one's attention deteriorates in patients with childhood chronic fatigue syndrome (CCFS). We conducted a study using a dual verbal task to assess allocation of attentional resources to two simultaneous activities (picking out vowels and reading for story comprehension) and functional magnetic resonance imaging. Patients exhibited a much larger area of activation, recruiting additional frontal areas. The right middle frontal gyrus (MFG), which is included in the dorsolateral prefrontal cort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 44 publications
1
33
0
Order By: Relevance
“…Thus, DMN synchronization in CFS was weaker than NC during the task, which more generally may be expected to increase the energy consumption required to perform tasks. Our observation of increased BOLD activation in CFS not balanced by increased BOLD inhibition elsewhere in the brain, together with similar observations in previous reports (Lange et al, 2005;Mizuno et al, 2015), provide support for this notion. It appears that CFS patients demand more BOLD activation to compensate for the more complex and unsynchronized brain activity/connectivity in and between different components of their central nervous system.…”
Section: Discussionsupporting
confidence: 92%
“…Thus, DMN synchronization in CFS was weaker than NC during the task, which more generally may be expected to increase the energy consumption required to perform tasks. Our observation of increased BOLD activation in CFS not balanced by increased BOLD inhibition elsewhere in the brain, together with similar observations in previous reports (Lange et al, 2005;Mizuno et al, 2015), provide support for this notion. It appears that CFS patients demand more BOLD activation to compensate for the more complex and unsynchronized brain activity/connectivity in and between different components of their central nervous system.…”
Section: Discussionsupporting
confidence: 92%
“…Decreases in motivational neural circuitry were associated with increases in mental and general fatigue and reductions in physical activity in adult CFS [ 81 ]. Previous fMRI studies with children and adolescents with CFS found changes in activities of the prefrontal and parietal regions during attentional control [ 82 ] and decreases in striatal activity involved in reward sensitivity and motivation [ 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, mental fatigue is known to be related to decreased motivation (Kitani, ; Mizuno et al, ) and is assessed by a reduction in voluntary activities (Yamato et al, ). For example, mental fatigue represents a failure to initiate and/or sustain mental tasks requiring self‐motivation (Chaudhuri and Behan, ), and in childhood chronic fatigue syndrome patients, the neuronal activity in the left dorsal inferior frontal gyrus was negatively correlated with motivation in which the neuronal activity had been shown to be positively correlated with the Chalder fatigue scale score in healthy volunteers (Mizuno et al, ). The present study demonstrates that, in the WLFST, nighttime spontaneous activity but not swimming time is decreased for a longer period after the 5‐min‐rest IWI procedure.…”
Section: Discussionmentioning
confidence: 99%